Prevalence of Hepatitis C, its Risk Factors, and Role of Preventive Measures among Healthcare Providers working at Primary Healthcare Centers (RHCs and BHUs) in District Gujrat Pakistan - Ghafoor, Amjad; Noor, Palwasha; Khattak, Iftikhar; Zafar, Alina; Ishtiaq, Hifza; Ahmed, Saqlain (Indus Journal of Bioscience Research, 2024)
Introduction: Healthcare providers (HCPs) have an elevated risk of hepatitis C virus (HCV) infection. HCV infection is an important threat to public health. According to WHO, it is anticipated that more than 3 % population in the world has an HCV infection. Methodology: This descriptive cross-sectional study was conducted at a primary healthcare facility. A total of 168 HCPs from RHCs and BHUs from District Gujarat were included in the study. A random sampling technique was used to collect data. The information was collected using a structured questionnaire. Results: Among 168 HCPs, 86.3% knew about the prevention of HCV, 29.2% had a history of needle prick, and 8.3% had a history of blood transfusion. Most of the healthcare providers (92.3%) used gloves, 82.7% took preventive measures while handling HCV-positive patients, and 1.8% of HCPs were found positive for HCV. Insignificant results (P>0.5) were found regarding designation (p=0.494), duration of employment (P-value = 1.000), and preventive measures (P-value = 0.457). Conclusion: The study concluded that the prevalence of HCV infection was 1.8% among healthcare providers. HCV infection was prevalent among LHVs/midwives or lab technicians/sanitary inspectors.